Analisis Lagu Bernuansa Jawa pada Perayaan Ekaristi di Gereja Stasi Kabar Gembira Kotabumi - Maria Angelika Intan Ristyaloka; Erizal Barnawi; Bian Pamungkas (Universitas Negeri Medan, 2025)
One of the most important parts that cannot be separated from the Eucharistic Celebration is the songs accompanying each procession. The songs used in the Eucharistic Celebration have various types. One popular form is the Inculturation song form. This study will discuss the use of the Javanese Inculturation song form used in the Eucharistic Celebration at the Kabar Gembira Catholic Church in Kotabumi using the Qualitative-Descriptive Research model. This study aims to analyze and describe the songs